2007
DOI: 10.1161/01.hyp.0000259739.64834.d4
|View full text |Cite
|
Sign up to set email alerts
|

Morning Blood Pressure Surge as a Destabilizing Factor of Atherosclerotic Plaque

Abstract: Abstract-Whether morning blood pressure surge influences the molecular mechanisms of plaque progression toward instability is not known. Recently, we have demonstrated enhanced activity of the ubiquitin-proteasome system in human plaques and evidenced that it is associated with inflammatory-induced plaque rupture. We evaluated the inflammatory infiltration and ubiquitin-proteasome activity in asymptomatic carotid plaques of hypertensive patients with different patterns of morning blood pressure surge. Plaques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 31 publications
2
57
0
4
Order By: Relevance
“…On the background of our previous report that excessive sleep-trough MS was an independent predictor of stroke in elderly Japanese hypertensive patients, 10 the present data are relevant to the interpretation of recent studies, which assessed the association between MS and target organ damage or cardiovascular events through the analysis of international databases, including subjects with different ethnic background, 11,[25][26][27] sometimes reaching discrepant conclusions. For example, recently, in The Progetto Ipertensione Umbria Monitoraggio Ambulatoriale (PIUMA) study, sleep-trough MS was not found to be a significant risk factor for cardiovascular events.…”
Section: Discussionmentioning
confidence: 75%
“…On the background of our previous report that excessive sleep-trough MS was an independent predictor of stroke in elderly Japanese hypertensive patients, 10 the present data are relevant to the interpretation of recent studies, which assessed the association between MS and target organ damage or cardiovascular events through the analysis of international databases, including subjects with different ethnic background, 11,[25][26][27] sometimes reaching discrepant conclusions. For example, recently, in The Progetto Ipertensione Umbria Monitoraggio Ambulatoriale (PIUMA) study, sleep-trough MS was not found to be a significant risk factor for cardiovascular events.…”
Section: Discussionmentioning
confidence: 75%
“…We reported previously that oxidative stress-dependent UPS overactivity contributes to the clinical instability of atherosclerotic plaques in hypertensive, 15 diabetic, 16 and symptomatic patients 17 by promoting plaque rupture induced by NF-B-dependent inflammation. Now, in the present report, we provide evidence for the critical involvement of UPS in the process of plaque stabilization realized by HRT in postmenopausal women.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, an exaggerated pressure load leads to fracture of the elastin fibers, to disorganization and hypertrophy of the muscular layers of the arterial wall, 28 and to plaque rupture. 29 These mechanisms might be particularly active in atherosclerotic arteries, 28 in the presence of oxidative stress, 29,30 or in older subjects with impaired baroreflexes. 31 …”
Section: Sleep-trough Morningmentioning
confidence: 99%